Wear-resistant domestic ceramic and preparation method thereof

CN122325209BActive Publication Date: 2026-10-23CHAOZHOU ZONGSHENG CERAMICS MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610744304.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-10-23
Estimated Expiration
2046-05-27

AI Technical Summary

Technical Problem

[0003]针对日用陶瓷耐磨性不足、改性粉体适配性差、坯釉结合稳定性弱的技术缺陷,本发明的目的在于提供一种耐磨日用陶瓷及其制备方法

Benefits of technology

[0022](1)本发明所公开的一种耐磨日用陶瓷及其制备方法通过采用钾长石、钠长石、高岭土、石英、滑石、莫来石复配制备素坯,各组分功能互补协同:高岭土提供优良塑性,保障坯体成型质量;石英构建刚性骨架,提升基体基础硬度;钾、钠长石充当助熔组分,降低烧结能耗;滑石调节坯体热膨胀系数,减少冷热形变开裂;莫来石具备高强耐磨特性,从基体层面提升陶瓷抗冲击、抗形变能力;搭配素烧工艺,可充分脱除坯体内部游离水分与有机杂质,使坯体预先固化定型,有效避免后续施釉、高温烧制过程中出现崩裂、变形问题,为釉层牢固附着奠定坚实结构基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a wear-resistant daily-use ceramic and a preparation method thereof, and belongs to the technical field of wear-resistant ceramics. The preparation method comprises the following steps: using potash feldspar, soda feldspar, kaolin, quartz, talc and mullite as raw materials to prepare a blank by means of body firing; using quartz, soda feldspar, talc, potash feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose and wear-resistant powder as raw materials to obtain a glaze slurry; the wear-resistant powder comprises hydroxyapatite, fluorite, calcite, zirconium silicate and TiO2@SiO2-Al2O3; the glaze slurry is applied to the surface of the blank, and the ceramic is obtained after drying and firing, so that the wear resistance of the ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wear-resistant ceramic technology, specifically relating to a wear-resistant daily-use ceramic and its preparation method. Background Technology

[0002] Ceramic products, whether building wall and floor tiles, sanitary ware, or everyday ceramics such as plates and bowls, are closely related to people's lives. In actual use, everyday ceramics are frequently subjected to friction, scratches, and daily bumps, making the glaze surface prone to scratches, loss of luster, and surface wear and peeling. Currently, most conventional everyday ceramics on the market are made from a mixture of basic mineral raw materials such as kaolin, feldspar, and quartz. The traditional body and glaze system itself has low hardness and limited wear resistance, making it difficult to adapt to high-frequency use conditions. To improve the wear resistance of ceramics, existing technologies often employ modification methods by directly doping the glaze with hard wear-resistant powders. Commonly used modifiers include single hard particles such as titanium dioxide and zirconium silicate. However, this modification method has significant drawbacks: on the one hand, hard powders are prone to agglomeration and uneven dispersion in the glaze slurry. After high-temperature sintering, the interfacial bonding strength between the powder and the glaze matrix is ​​weak, and the wear-resistant particles are prone to detachment during use, resulting in the wear-resistant strengthening effect not meeting expectations. On the other hand, modified powders with a single coating structure have poor structural stability and insufficient thermal shock resistance, making them prone to microcracks during ceramic firing and subsequent use, further exacerbating wear and breakage problems. Meanwhile, existing wear-resistant ceramic formulations generally suffer from unreasonable functional component ratios, lack mineralized fluxing agents and toughening and reinforcing mineral components, have poor integration between the hard wear-resistant phase and the glaze matrix, have many internal pores in the glaze layer, and lack structural density. Furthermore, most preparation processes do not finely control the green body forming, powder refining, and segmented sintering processes, resulting in low green body structural strength. Internal stress is easily generated at the green body-glaze interface, which can easily lead to defects such as glaze peeling and edge chipping, making it impossible to simultaneously achieve high wear resistance, structural strength, and finished product yield. Summary of the Invention

[0003] In view of the technical defects of daily-use ceramics such as insufficient wear resistance, poor compatibility of modified powders, and weak bonding stability of body and glaze, the purpose of this invention is to provide a wear-resistant daily-use ceramic and its preparation method.

[0004] The objective of this invention can be achieved through the following technical solutions:

[0005] A method for preparing wear-resistant daily-use ceramics includes the following steps:

[0006] S1. A blank is prepared by firing potassium feldspar, sodium feldspar, kaolin, quartz, talc, and mullite as raw materials.

[0007] S2. A glaze slurry is obtained using quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, and wear-resistant powder as raw materials; the wear-resistant powder includes hydroxyapatite, fluorite, calcite, zirconium silicate, and TiO2@SiO2-Al2O3.

[0008] S3. Apply the glaze slurry to the surface of the unglazed body, dry it, and then fire it to obtain the wear-resistant daily ceramic.

[0009] As a preferred technical solution of the present invention, in step S1, the mass ratio of potassium feldspar, sodium feldspar, kaolin, quartz, talc, and mullite is 22-30:12-22:28-48:20-25:1-5:24-34; the bisque firing refers to holding at 800-900℃ for 3-5 hours.

[0010] As a preferred technical solution of the present invention, in step S2, the mass ratio of quartz, sodium feldspar, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, and wear-resistant powder is 15-25:18-24:14-18:7-9:1-3:13-18:0.4-0.6:8-12.

[0011] As a preferred embodiment of the present invention, in step S3, the glazing amount is 65-85 g / m². 2 .

[0012] As a preferred embodiment of the present invention, step S2, the method for preparing the wear-resistant powder includes the following steps:

[0013] Hydroxyapatite, fluorite, and calcite were mixed and crushed into powder. Zirconium silicate, TiO2@SiO2-Al2O3, and deionized water were added, and the mixture was ball-milled and sieved to obtain wear-resistant powder.

[0014] As a preferred technical solution of the present invention, the ball milling refers to ball milling with zirconia balls as the ball milling medium for 5-7 hours, the ball milling speed is 250-350 r / min, and the ball-to-material ratio of the ball milling is 2-3:1;

[0015] The mass ratio of hydroxyapatite, fluorite, calcite, zirconium silicate, TiO2@SiO2-Al2O3 and deionized water is 40-50:20-30:20-30:5-10:3-8:50-80.

[0016] As a preferred embodiment of the present invention, the preparation method of TiO2@SiO2-Al2O3 includes the following steps:

[0017] Nano-TiO2 was ultrasonically dispersed in an aqueous solution of sodium hexametaphosphate. The pH of the system was adjusted to 9.0-9.5. Under constant temperature heating conditions of 65-70℃, sodium metasilicate aqueous solution was added dropwise while stirring to adjust the pH of the system to 8.5-9.0. The mixture was stirred and aged. Sodium aluminate aqueous solution was added dropwise while stirring to adjust the pH of the system to 7.5-8.0. The mixture was stirred and aged. The pH of the system was adjusted to 7.0-7.2. The mixture was stirred, filtered, and the solid phase was collected, washed, vacuum dried, and pulverized to obtain TiO2@SiO2-Al2O3.

[0018] As a preferred embodiment of the present invention, the mass ratio of the nano-TiO2, sodium hexametaphosphate aqueous solution, sodium metasilicate aqueous solution, and sodium aluminate aqueous solution is 1:9-11:1.8-2.2:1.3-1.6.

[0019] As a preferred technical solution of the present invention, in step S3, the firing refers to heating from room temperature to 650-750°C at a rate of 0.5-1.0°C / min, then heating to 1200-1280°C at a rate of 1.5-2.0°C / min, holding at that temperature for 2-3 hours, slowly cooling to 800°C at a rate of 1.0-1.5°C / min, and then naturally cooling to room temperature with the furnace.

[0020] Another object of the present invention is to provide a wear-resistant daily-use ceramic.

[0021] The beneficial effects of this invention are:

[0022] (1) The wear-resistant daily ceramic and its preparation method disclosed in this invention are prepared by using potassium feldspar, sodium feldspar, kaolin, quartz, talc and mullite to prepare the green body. Each component has complementary and synergistic functions: kaolin provides excellent plasticity and ensures the quality of green body forming; quartz constructs a rigid skeleton and improves the basic hardness of the matrix; potassium and sodium feldspar act as fluxing components to reduce sintering energy consumption; talc adjusts the coefficient of thermal expansion of the green body and reduces cold and hot deformation cracking; mullite has high strength and wear resistance, which improves the impact resistance and deformation resistance of ceramics from the matrix level; combined with the bisque firing process, the free water and organic impurities inside the green body can be fully removed, so that the green body is pre-cured and shaped, effectively avoiding the problems of cracking and deformation during subsequent glazing and high-temperature firing, and laying a solid structural foundation for the firm adhesion of the glaze layer.

[0023] (2) The wear-resistant daily ceramic and its preparation method disclosed in this invention abandon the single hard powder modification mode and adopt a multi-component wear-resistant powder compound of hydroxyapatite, fluorite, calcite, zirconium silicate and TiO2@SiO2-Al2O3. Each component has a clear division of labor and complementary performance: zirconium silicate, as the core hard wear-resistant filler, greatly improves the surface hardness of the glaze and resists daily friction and scratches; hydroxyapatite improves the toughness of the glaze layer and reduces the probability of ceramic damage from impacts; fluorite and calcite play a role in high-temperature mineralization fluxing, strengthen the interfacial bonding force between wear-resistant particles and glaze matrix, and avoid wear-resistant phase detachment failure; core-shell modified powder fills the micropores of the glaze layer, improves the density of the glaze layer, effectively weakens the thermal stress at the body-glaze interface during the slow cooling stage of sintering, greatly reduces the risk of glaze delamination and delamination cracking, strengthens the overall bonding strength of body-glaze, and improves the yield and structural durability of finished products.

[0024] (3) The wear-resistant daily ceramic and its preparation method disclosed in this invention enhance the wear resistance of the glaze layer by introducing a titanium core-silicon-aluminum composite core-shell structure of TiO2@SiO2-Al2O3: Rutile nano-titanium dioxide is selected as the core matrix. This material is resistant to high temperature, chemically stable, and has a regular grain structure. It has a certain hardness and structural strength. Using monodisperse nano-titanium dioxide as the coating core can avoid the premature agglomeration of the powder itself and provide a reliable carrier for the uniform attachment and layer-by-layer growth of silicon and aluminum active species. The preparation process adjusts the pH of the system in stages and maintains a constant reaction temperature. Silicon source and aluminum source precursors are added dropwise in sequence. The weakly alkaline constant temperature environment can slowly stimulate the hydrolysis reaction of the precursor and gradually generate active colloidal groups with silanol and aluminum hydroxyl groups. This avoids the problem of free impurities and uneven coating thickness caused by rapid hydrolysis of one-time feeding. The stepwise aging process gives the groups sufficient time for adsorption and arrangement, allowing silicon and aluminum active substances to be deposited in an orderly manner on the nano-titanium dioxide core. A continuous and complete pre-coating layer is formed on the surface of titanium dioxide. Dehydration condensation forms Si-O-Al covalent cross-linking bonds, while Ti-O-Si bonds are formed at the shell-core interface, firmly anchoring the silicon-aluminum composite shell to the surface of the titanium dioxide core. The Si-O-Al bridging bonds interweave and overlap, together with the Si-O-Si and Al-O-Al bonds, to build a spatially continuous three-dimensional network composite framework. The internal structure of the shell is dense and compact, without loose fragments or obvious interface defects. When incorporated into the glaze slurry, it exhibits excellent dispersibility and can uniformly fill the micropores inside the glaze layer, improving the overall density of the glaze surface. After high-temperature sintering, the core-shell powder and the glaze matrix interface are tightly fused, forming a high-strength integrated structure. When the ceramic is subjected to friction, scratching, and wear, the dense three-dimensional framework can effectively resist external cutting, scratching, and squeezing, buffering the impact of wear, reducing the loss of material peeling off the glaze surface, significantly reducing the wear rate, and achieving a significant improvement in the wear resistance of daily-use ceramics. Detailed Implementation

[0025] The claims of the present invention will be further described in detail below with reference to specific embodiments, but this does not constitute any limitation on the present invention. Any limited modifications made by any person within the scope of protection of the claims of the present invention are still within the scope of protection of the claims of the present invention.

[0026] Example 1

[0027] A method for preparing a wear-resistant daily-use ceramic includes the following steps:

[0028] S1. Potassium feldspar, sodium feldspar, kaolin, quartz, talc, and mullite are mixed and dry-milled, then deionized water is added and wet-milled. The mixture is passed through a 200-mesh sieve to obtain a blank. After aging, kneading, rolling, drying, and bisque firing, a bisque is obtained. The dry ball milling refers to milling with alumina balls as the milling medium for 30 minutes at a milling speed of 400 r / min, with a ball-to-material ratio of 2:1.0. The wet ball milling is performed at a milling speed of 200 r / min for 3 hours. The mass ratio of potassium feldspar, sodium feldspar, kaolin, quartz, talc, mullite, and deionized water is 22:12:28:20:1:24:75. Bisque firing refers to holding at 800℃ for 5 hours.

[0029] S2. Take quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, wear-resistant powder, and deionized water, mix and ball mill, pass through a 300-mesh sieve to remove iron, and obtain a glaze slurry; the mass ratio of quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, wear-resistant powder, and deionized water is 15:18:14:7:1:13:0.4:8:70; the ball milling refers to ball milling with alumina balls as the milling medium for 5 hours, the ball milling speed is 200 r / min, and the ball-to-material ratio is 2:1.3;

[0030] The method for preparing the wear-resistant powder includes the following steps:

[0031] Hydroxyapatite, fluorite, and calcite were mixed and crushed into powder. Zirconium silicate, TiO2@SiO2-Al2O3, and deionized water were added and mixed. The mixture was then ball-milled and passed through a 300-mesh sieve to obtain wear-resistant powder. The ball milling refers to ball milling with zirconia balls as the milling medium for 5 hours at a milling speed of 250 r / min. The ball-to-material ratio was 2:1. The mass ratio of hydroxyapatite, fluorite, calcite, zirconium silicate, TiO2@SiO2-Al2O3, and deionized water was 40:20:20:5:3:50.

[0032] The preparation method of the TiO2@SiO2-Al2O3 includes the following steps:

[0033] Rutile nano-TiO2 powder was ultrasonically dispersed in a 0.15% (w / w) sodium hexametaphosphate aqueous solution. The pH of the system was adjusted to 9.0 using a 0.5 mol / L sodium hydroxide solution. Under constant temperature heating at 65℃, a 5% (w / w) sodium metasilicate aqueous solution (modulus 1.0) was added dropwise while stirring. The pH of the system was adjusted to 8.5 using a 0.5 mol / L sulfuric acid solution. Stirring was continued for 30 min, and the mixture was allowed to stand for 1 h. Then, a 4% (w / w) sodium aluminate aqueous solution was added dropwise while stirring, and the pH of the system was adjusted to [missing value]. 7.5, continue stirring for 30 min, let stand and age for 1 h, adjust the pH of the system to 7.0 with 0.5 mol / L sulfuric acid solution, continue stirring for 5 min, filter, collect the solid phase and wash it successively with deionized water, anhydrous ethanol and deionized water, then vacuum dry, and put it into an air jet mill to be pulverized at a pulverizing pressure of 0.6 MPa for 8 min to obtain TiO2@SiO2-Al2O3; the mass ratio of the rutile nano TiO2 powder, sodium hexametaphosphate aqueous solution, sodium metasilicate aqueous solution and sodium aluminate aqueous solution is 1:9:1.8:1.3;

[0034] S3. Apply the glaze slurry to the surface of the unglazed body, allow it to air dry naturally, and then fire it to obtain the wear-resistant daily-use ceramic; the glaze application amount is 65g / m². 2 The firing process refers to heating the furnace from room temperature to 650°C at a rate of 0.5°C / min, then heating it to 1200°C at a rate of 1.5°C / min, holding it at that temperature for 2 hours, and then slowly cooling it to 800°C at a rate of 1.0°C / min, before allowing it to cool naturally to room temperature.

[0035] Example 2

[0036] A method for preparing a wear-resistant daily-use ceramic includes the following steps:

[0037] S1. Potassium feldspar, sodium feldspar, kaolin, quartz, talc, and mullite are mixed and dry-milled, then deionized water is added and wet-milled. The mixture is passed through a 250-mesh sieve to obtain a blank. After aging, kneading, rolling, drying, and bisque firing, a bisque is obtained. The dry-milling refers to milling with alumina balls as the milling medium for 35 minutes at a milling speed of 450 r / min, with a ball-to-material ratio of 2:1.2. The wet-milling refers to milling at a milling speed of 250 r / min for 3.5 hours. The mass ratio of potassium feldspar, sodium feldspar, kaolin, quartz, talc, mullite, and deionized water is 26:17:38:23:3:29:95. Bisque firing refers to holding at 850℃ for 4 hours.

[0038] S2. Take quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, wear-resistant powder, and deionized water, mix and ball mill, pass through a 350-mesh sieve to remove iron, and obtain a glaze slurry; the mass ratio of quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, wear-resistant powder, and deionized water is 20:20:16:8:2:15:0.5:10:75; the ball milling refers to ball milling with alumina balls as the milling medium for 5.5 hours, the ball milling speed is 250 r / min, and the ball-to-material ratio is 2:1.4;

[0039] The method for preparing the wear-resistant powder includes the following steps:

[0040] Hydroxyapatite, fluorite, and calcite were mixed and crushed into powder. Zirconium silicate, TiO2@SiO2-Al2O3, and deionized water were added and mixed. The mixture was then ball-milled and passed through a 350-mesh sieve to obtain wear-resistant powder. The ball milling refers to ball milling with zirconia balls as the milling medium for 6 hours at a milling speed of 300 r / min. The ball-to-material ratio was 2.5:1. The mass ratio of hydroxyapatite, fluorite, calcite, zirconium silicate, TiO2@SiO2-Al2O3, and deionized water was 45:25:25:8:5:65.

[0041] The preparation method of the TiO2@SiO2-Al2O3 includes the following steps:

[0042] Rutile nano-TiO2 powder was ultrasonically dispersed in a 0.15% (w / w) sodium hexametaphosphate aqueous solution. The pH of the system was adjusted to 9.3 using a 0.5 mol / L sodium hydroxide solution. Under constant temperature heating at 68℃, a 5% (w / w) sodium metasilicate aqueous solution (modulus 1.0) was added dropwise while stirring. The pH of the system was adjusted to 8.7 using a 0.5 mol / L sulfuric acid solution. Stirring was continued for 35 min, followed by standing and aging for 1.5 h. Then, a 4% (w / w) sodium aluminate aqueous solution was added dropwise while stirring, and the pH of the system was adjusted to [missing value]. 7.8, continue stirring for 35 min, let stand and age for 1.5 h, adjust the pH of the system to 7.1 with 0.5 mol / L sulfuric acid solution, continue stirring for 8 min, filter, collect the solid phase and wash it successively with deionized water, anhydrous ethanol and deionized water, then vacuum dry, and put it into an air jet mill to be pulverized at a pulverizing pressure of 0.7 MPa for 6 min to obtain TiO2@SiO2-Al2O3; the mass ratio of the rutile nano TiO2 powder, sodium hexametaphosphate aqueous solution, sodium metasilicate aqueous solution and sodium aluminate aqueous solution is 1:10:2.0:1.5;

[0043] S3. Apply the glaze slurry to the surface of the unglazed body, allow it to air dry naturally, and then fire it to obtain the wear-resistant daily-use ceramic; the glaze application amount is 75g / m². 2The firing process refers to heating the furnace from room temperature to 700°C at a rate of 0.5°C / min, then heating it to 1240°C at a rate of 2.0°C / min, holding it at that temperature for 2.5 hours, slowly cooling it to 800°C at a rate of 1.0°C / min, and then naturally cooling it to room temperature with the furnace.

[0044] Example 3

[0045] A method for preparing a wear-resistant daily-use ceramic includes the following steps:

[0046] S1. Potassium feldspar, sodium feldspar, kaolin, quartz, talc, and mullite are mixed and dry-milled, then deionized water is added and wet-milled. The mixture is passed through a 300-mesh sieve to obtain a blank. After aging, kneading, rolling, drying, and bisque firing, a bisque is obtained. The dry-milling refers to milling with alumina balls as the milling medium for 40 minutes at a milling speed of 500 r / min, with a ball-to-material ratio of 2:1.5. The wet-milling refers to milling at a milling speed of 300 r / min for 4 hours. The mass ratio of potassium feldspar, sodium feldspar, kaolin, quartz, talc, mullite, and deionized water is 30:22:48:25:5:34:115. Bisque firing refers to holding at 900℃ for 5 hours.

[0047] S2. Take quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, wear-resistant powder, and deionized water, mix and ball mill, pass through a 300-400 mesh sieve to remove iron, and obtain a glaze slurry; the mass ratio of quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, wear-resistant powder, and deionized water is 25:24:18:9:3:18:0.6:12:80; the ball milling refers to ball milling with alumina balls as the ball milling medium for 6 hours, the ball milling speed is 300 r / min, and the ball-to-material ratio of the ball milling is 2:1.5;

[0048] The method for preparing the wear-resistant powder includes the following steps:

[0049] Hydroxyapatite, fluorite, and calcite were mixed and crushed into powder. Zirconium silicate, TiO2@SiO2-Al2O3, and deionized water were added and mixed. The mixture was then ball-milled and passed through a 400-mesh sieve to obtain wear-resistant powder. The ball milling refers to ball milling with zirconia balls as the milling medium for 7 hours at a milling speed of 350 r / min. The ball-to-material ratio was 3:1. The mass ratio of hydroxyapatite, fluorite, calcite, zirconium silicate, TiO2@SiO2-Al2O3, and deionized water was 50:30:30:10:8:80.

[0050] The preparation method of the TiO2@SiO2-Al2O3 includes the following steps:

[0051] Rutile nano-TiO2 powder was ultrasonically dispersed in a 0.15% (w / w) sodium hexametaphosphate aqueous solution. The pH of the system was adjusted to 9.5 using a 0.5 mol / L sodium hydroxide solution. Under constant temperature heating at 70℃, a 5% (w / w) sodium metasilicate aqueous solution (modulus 1.0) was added dropwise while stirring. The pH of the system was adjusted to 9.0 using a 0.5 mol / L sulfuric acid solution. Stirring was continued for 40 min, and the mixture was allowed to stand for 2 h. Then, a 4% (w / w) sodium aluminate aqueous solution was added dropwise while stirring, and the pH of the system was adjusted to 8 using a 0.5 mol / L sulfuric acid solution. 0.0, continue stirring for 40 min, let stand and age for 2 h, adjust the pH of the system to 7.2 with 0.5 mol / L sulfuric acid solution, continue stirring for 10 min, filter, collect the solid phase and wash it successively with deionized water, anhydrous ethanol and deionized water, then vacuum dry, and put it into an air jet mill to be pulverized at a pulverizing pressure of 0.8 MPa for 5 min to obtain TiO2@SiO2-Al2O3; the mass ratio of the rutile nano TiO2 powder, sodium hexametaphosphate aqueous solution, sodium metasilicate aqueous solution and sodium aluminate aqueous solution is 1:11:2.2:1.6;

[0052] S3. Apply the glaze slurry to the surface of the unglazed body, allow it to air dry naturally, and then fire it to obtain the wear-resistant daily-use ceramic; the glaze application amount is 85g / m². 2 The firing process refers to heating from room temperature to 750°C at a rate of 1.0°C / min, then heating to 1280°C at a rate of 2.0°C / min, holding at that temperature for 2 hours, slowly cooling to 800°C at a rate of 1.5°C / min, and then naturally cooling to room temperature with the furnace.

[0053] Comparative Example 1

[0054] The difference from Example 2 is that fluorite is not added to the wear-resistant powder.

[0055] Comparative Example 2

[0056] The difference from Example 2 is that calcite is not added to the wear-resistant powder.

[0057] Comparative Example 3

[0058] The difference from Example 2 is that zirconium silicate is not added to the wear-resistant powder.

[0059] Comparative Example 4

[0060] The difference from Example 2 is that the wear-resistant powder includes hydroxyapatite, fluorite, calcite, zirconium silicate, and TiO2@SiO2;

[0061] The preparation method of the TiO2@SiO2 includes the following steps:

[0062] Rutile nano-TiO2 powder was ultrasonically dispersed in a 0.15% sodium hexametaphosphate aqueous solution. The pH of the system was adjusted to 9.3 using a 0.5 mol / L sodium hydroxide solution. Under constant temperature heating at 68℃, a 5% sodium metasilicate aqueous solution (modulus 1.0) was added dropwise while stirring. The pH of the system was adjusted to 8.7 using a 0.5 mol / L sulfuric acid solution. Stirring was continued for 35 min, and the mixture was allowed to stand for 1.5 h. The pH of the system was then adjusted to 7.1 using a 0.5 mol / L sulfuric acid solution, and stirring was continued for 8 min. The mixture was then filtered, and the collected solid phase was washed sequentially with deionized water, anhydrous ethanol, and deionized water. After vacuum drying, the solid phase was pulverized in an air jet mill at a pulverizing pressure of 0.7 MPa for 6 min to obtain TiO2@SiO2. The mass ratio of the rutile nano-TiO2 powder, sodium hexametaphosphate aqueous solution, and sodium metasilicate aqueous solution was 1:10:2.0.

[0063] Comparative Example 5

[0064] The difference from Example 2 is that the wear-resistant powder includes hydroxyapatite, fluorite, calcite, zirconium silicate, and TiO2@Al2O3;

[0065] The preparation method of the TiO2@Al2O3 includes the following steps:

[0066] Rutile nano-TiO2 powder was ultrasonically dispersed in a 0.15% (w / w) sodium hexametaphosphate aqueous solution. The pH of the system was adjusted to 9.3 using a 0.5 mol / L sodium hydroxide solution. Under constant temperature heating at 68℃, a 4% (w / w) sodium aluminate aqueous solution was added dropwise while stirring. The pH of the system was adjusted to 7.8 using a 0.5 mol / L sulfuric acid solution. Stirring was continued for 35 min, and the mixture was allowed to stand for 1.5 h. The pH of the system was then adjusted to 7.1 using a 0.5 mol / L sulfuric acid solution, and stirring was continued for 8 min. The mixture was then filtered, and the collected solid phase was washed successively with deionized water, anhydrous ethanol, and deionized water. After vacuum drying, the solid phase was pulverized in an air jet mill at a pulverizing pressure of 0.7 MPa for 6 min to obtain TiO2@Al2O3. The mass ratio of the rutile nano-TiO2 powder, sodium hexametaphosphate aqueous solution, and sodium aluminate aqueous solution was 1:10:1.5.

[0067] Performance testing

[0068] 1. Take ceramics prepared in Examples 1-3 and Comparative Examples 1-5 respectively, and prepare fragments of the same thickness at the same location, with dimensions of 50 mm in length and 50 mm in width as samples. Grind the edges of the samples with 400-grit sandpaper to a 45-degree chamfer to ensure the sample surface is free of cracks, bubbles, and obvious defects, and the glaze is intact and uniform. Clean the obtained samples with analytical grade anhydrous ethanol in an ultrasonic cleaner with a power of 100W and a frequency of 40kHz for 5 minutes, then place them in a constant temperature drying oven at 105℃ for 2 hours. After removal, cool them to room temperature in a desiccator. Weigh 6 mm diameter stainless steel grinding balls with a hardness of HRC60-62 and 80 mesh with a purity ≥99% according to a mass ratio of 2:1:4. White corundum and deionized water with a conductivity ≤10μS / cm were mixed evenly to prepare the grinding media. 50g of the mixed grinding media was prepared for each batch of tests. The pretreated sample was fixed with the glaze side facing up in the sample holder with a rubber pad, ensuring that the sample was firm and not loose and that the glaze surface was horizontal. Only one sample was placed in each holder. 10g of the mixed grinding media was evenly placed on the surface of each sample. The wear resistance tester was started, the speed was set to 300r / min and the load was 10N. The continuous rotation mode was adopted, and the machine was stopped once every 50 revolutions. The surface of the sample was observed with a stereomicroscope to see if the first visible wear appeared. If there was no wear, the test continued. If wear appeared, the test of the sample was stopped immediately and the total number of revolutions was recorded. The test results are shown in Table 1 below.

[0069] Table 1

[0070]

[0071] 2. Take ceramics prepared in Examples 1-3 and Comparative Examples 1-5 respectively, and prepare fragments of the same thickness at the same location, with dimensions of 50 mm in length and 50 mm in width as samples. The edges of the samples are polished to a 45-degree chamfer using 400-grit sandpaper to ensure the sample surface is free of cracks, bubbles, and obvious defects, and the glaze is intact and uniform. Clean the obtained samples with analytical grade anhydrous ethanol in a 100W, 40kHz ultrasonic cleaner for 5 minutes, then place them in a constant temperature drying oven at 105℃ for 2 hours. After removal, cool them to room temperature in a desiccator, and weigh each sample using an electronic balance. Before friction, the initial mass of the ceramic sample is M0. A GCr15 steel ball is securely installed in the fixture of the testing machine, ensuring the ball is not loose or scratched. The cooled and weighed ceramic sample is horizontally fixed in the lower friction disc fixture, with the glaze facing upwards. A ball-disc friction machine is used, with a load of 5N, a rotation speed of 300r / min, a friction radius of 15mm, and a test time of 30min set. The upper fixture is slowly lowered so that the steel ball makes vertical contact with the ceramic glaze surface, and the load is applied smoothly to the set value. The equipment is started to begin timing the friction. The operating status of the equipment is observed throughout the test, and the sample and rotating parts must not be touched. After the set time of 30min is reached, the equipment automatically stops. The upper fixture is slowly lifted, and the worn ceramic sample is removed. The surface of the sample is gently wiped with lint-free paper to remove friction debris without damaging the glaze substrate. The sample is then ultrasonically cleaned again with anhydrous ethanol for 5min, dried, and cooled to room temperature. The mass M1 of each sample after friction is weighed, and the wear rate is calculated.

[0072] Wear rate (%) = [(M0-M1) / M0] × 100%;

[0073] The test results are shown in Table 2 below.

[0074] Table 2

[0075]

[0076] The test results above show that the ceramic materials prepared in Examples 1-3 of this invention have good wear resistance. Comparative Example 1 lacks fluorite, and its removal reduces the density of the glaze layer and decreases its wear resistance. Comparative Example 2 lacks calcite to optimize the pore structure of the glaze layer and assist in mineralization and consolidation, resulting in decreased wear resistance. Comparative Example 3 lacks zirconium silicate reinforcing phase, leading to a significant decrease in wear resistance. Comparative Examples 4 and 5 are only single-shell structures, lacking Si-O-Al cross-linking bonds, and their structural stability is weaker than that of the silicon-aluminum composite shell, resulting in decreased wear resistance.

[0077] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, features in the embodiments of the present invention can be combined with each other unless otherwise specified.

Claims

1. A method for preparing wear-resistant daily-use ceramics, characterized in that, Includes the following steps: S1. A blank is prepared by firing potassium feldspar, sodium feldspar, kaolin, quartz, talc, and mullite as raw materials. S2. A glaze slurry is obtained using quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, and wear-resistant powder as raw materials; the wear-resistant powder includes hydroxyapatite, fluorite, calcite, zirconium silicate, and TiO2@SiO2-Al2O3. The mass ratio of quartz, albite, talc, potassium feldspar, nano zinc oxide, kaolin, sodium carboxymethyl cellulose, and wear-resistant powder is 15-25:18-24:14-18:7-9:1-3:13-18:0.4-0.6:8-12. The mass ratio of hydroxyapatite, fluorite, calcite, zirconium silicate, TiO2@SiO2-Al2O3 and deionized water used to prepare the wear-resistant powder is 40-50:20-30:20-30:5-10:3-8:50-80; S3. Apply the glaze slurry to the surface of the unglazed body, dry it, and then fire it to obtain the wear-resistant daily ceramic.

2. The method for preparing a wear-resistant daily-use ceramic according to claim 1, characterized in that, In step S1, the mass ratio of potassium feldspar, sodium feldspar, kaolin, quartz, talc, and mullite is 22-30:12-22:28-48:20-25:1-5:24-34; the bisque firing refers to holding at 800-900℃ for 3-5 hours.

3. The method for preparing a wear-resistant daily-use ceramic according to claim 1, characterized in that, In step S3, the glazing amount is 65-85 g / m³. 2 .

4. The method for preparing a wear-resistant daily-use ceramic according to claim 1, characterized in that, In step S2, the method for preparing the wear-resistant powder includes the following steps: Hydroxyapatite, fluorite, and calcite were mixed and crushed into powder. Zirconium silicate, TiO2@SiO2-Al2O3, and deionized water were added, and the mixture was ball-milled and sieved to obtain wear-resistant powder.

5. The method for preparing a wear-resistant daily-use ceramic according to claim 4, characterized in that, The ball milling refers to ball milling with zirconia balls as the milling medium for 5-7 hours, with a milling speed of 250-350 r / min, and a ball-to-material ratio of 2-3:

1.

6. The method for preparing a wear-resistant daily-use ceramic according to claim 4, characterized in that, The preparation method of the TiO2@SiO2-Al2O3 includes the following steps: Nano-TiO2 was ultrasonically dispersed in an aqueous solution of sodium hexametaphosphate. The pH of the system was adjusted to 9.0-9.

5. Under constant temperature heating conditions of 65-70℃, sodium metasilicate aqueous solution was added dropwise while stirring to adjust the pH of the system to 8.5-9.

0. The mixture was stirred and aged. Sodium aluminate aqueous solution was added dropwise while stirring to adjust the pH of the system to 7.5-8.

0. The mixture was stirred and aged. The pH of the system was adjusted to 7.0-7.

2. The mixture was stirred, filtered, and the solid phase was collected, washed, vacuum dried, and pulverized to obtain TiO2@SiO2-Al2O3.

7. The method for preparing a wear-resistant daily-use ceramic according to claim 6, characterized in that, The mass ratio of the nano-TiO2, sodium hexametaphosphate aqueous solution, sodium metasilicate aqueous solution, and sodium aluminate aqueous solution is 1:9-11:1.8-2.2:1.3-1.

6.

8. The method for preparing a wear-resistant daily-use ceramic according to claim 1, characterized in that, In step S3, the firing process refers to heating from room temperature to 650-750°C at a rate of 0.5-1.0°C / min, then heating to 1200-1280°C at a rate of 1.5-2.0°C / min, holding at that temperature for 2-3 hours, then slowly cooling to 800°C at a rate of 1.0-1.5°C / min, and finally cooling naturally to room temperature with the furnace.

9. A wear-resistant daily-use ceramic, characterized in that, It is prepared using the method for preparing a wear-resistant daily-use ceramic according to any one of claims 1-8.

Citation Information

Patent Citations

  • Core-shell structure high-electric-strength titanium oxide-based dielectric powder as well as preparation method and application thereof

    CN111732431A

  • KR20220162915A